2011
DOI: 10.1007/s11232-011-0139-2
|View full text |Cite
|
Sign up to set email alerts
|

Heisenberg doubles of quantized Poincaré algebras

Abstract: We briefly analyze some general questions concerning the twist deformation of the Heisenberg double. We reconsider Heisenberg doubles based on quantized Poincaré (Hopf ) algebras as illustrative examples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…In this paper, we investigated three Heisenberg doubles related to the two types of noncommutative Snyder models. The Heisenberg double construction was widely investigated for other noncommutative spacetimes [1][2][3][4][5], but not yet (to our knowledge) for the Snyder space. Therefore, this work offers the first study on Heisenberg doubles for the Snyder model, as well as for the extended Snyder model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this paper, we investigated three Heisenberg doubles related to the two types of noncommutative Snyder models. The Heisenberg double construction was widely investigated for other noncommutative spacetimes [1][2][3][4][5], but not yet (to our knowledge) for the Snyder space. Therefore, this work offers the first study on Heisenberg doubles for the Snyder model, as well as for the extended Snyder model.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that in the limit of β → 0, the coproducts for the momenta ( 5) and (10) reduce to ∆p i = 1 ⊗ p j + p i ⊗ 1. For β = 0 (classical case), there exists full-duality between algebra A generators x i , M ij and group elements p i , Λ ij (where Λ ij are the matrix elements of Lorentz matrices; see, e.g., [1][2][3][4][5]).…”
Section: Different Realization For Coproducts Of Momentamentioning
confidence: 99%
See 1 more Smart Citation
“…The Lie algebra an(n), when its generators are identified with space-time coordinates, is known in the literature as the n + 1-dimensional κ-Minkowski space. For further technical details on κ-deformations the interested reader can consult [37][38][39][40][41][42][43][44][45][46]. The main goal of this Section will be to show that starting from minimal ingredients, namely the structures constants the Lie algebra an(n),…”
Section: Deforming Momentum Space To the An (N) Groupmentioning
confidence: 99%
“…Later in [9], using a formalism developed in [10], it was shown that this construction can be extended to include also a κ-deformation, by passing from an algebra so(1, N ) to an algebra so(1, N ; g) with generatorŝ X µν , in which the metric η µν is changed into a nondiagonal metric g µν . In that paper, only the Weyl realization of the Hopf algebra was considered and the coproduct and twist were calculated only in that case.…”
Section: Introductionmentioning
confidence: 99%